CONTENT OF HEAVY METALS IN SOILS OF OIL-POLLUTED AREAS OF PRE-CARPATHIAN - Lopushnyak, V.; Hrytsulyak, H.; Tonkha, O.; Menshov, O.; Pikovsʹka, O.; Sychevsʹkyy, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article highlights the results of research on the content of heavy metals in sod-podzolic soils of oil-contaminated areas of Ivano-Frankivsk region. Contamination of soils with petroleum products causes severe ecological consequences for ecosystems. The aim of the research was to study the peculiarities of the accumulation of heavy metals in the soil, underground part and vegetative mass of sylphia perforated in the conditions of cultivation in oil-contaminated areas. The content of mobile forms of heavy metals in soils did not exceed the norms in all variants of the experiment. During the cultivation of Sylphia perfoliatum, it grew in a number: cadmium → nickel → cobalt → lead. The concentration of heavy metals in the soil was determined, which reflects the change in the content of the element in the test soil relative to the content of metals in the background soil. The coefficients of concentration of mobile forms of heavy metals in oil-contaminated soil for the cultivation of perforated sylphia for the application of fertilizers based on sewage sludge and compost based on them increased in a number: cobalt → lead → nickel → cadmium. Peculiarities of heavy metals accumulation in the vegetative mass of perforated sylphia have been established. Indices of intra-tissue heavy metal contamination of the root system of sylphia perforated with the introduction of sewage sludge increase in the following series: cadmium → nickel → lead → cobalt. The maximum indices of contamination of sylphia roots permeated with cadmium, nickel and cobalt are observed for the introduction into the soil of ERUs at a rate of 40 t / ha and N10P14K58, lead – for the application of compost at a rate of 30 t/ha and N30K55. The lowest indices of intratissue contamination with heavy metals of the roots of sylphia perfoliatum were noted for the application of fertilizer N60P60K60.